STUDY ON THE STRESS DISTRIBUTION OF FASTENING BOLTS OFSTEAM TURBINE CYLINDER BASED ON FINITE ELEMENT ANALYSIS - LIU ChangFu; CAI WenHe; DAI XiaoHao; CHEN Xin; DONG ShuQing; DU ShuangMing; NING YuHeng (Jixie qiangdu)
The intermediate pressure outer cylinder of steam-turbine of new units fractured during the 168 h running. The cracks were also found on the other bolts used on the intermediate pressure outer cylinder. It showed by the failure analysis that the brittle fracture occurred because of the high axial stress. The stress distribution was studied based on finite element analysis.The full screw thread and fine grid blocks were used to gain the higher calculation accuracy. It said that the stress of the screw thread was closely influenced by the stress of the mean stress of screw and the stress-strain curve. The force on the three screw threads which near the screw was higher than other screw threads.The maximum stress on the screw threads was 2.5 times of the screw and reached 82.8% of yield strength at the operating condition. The loading process was simulated and it showed that the stess was influenced by the loading process. Considering the service condition of the bolts,the fracture of the bolts was mainly caused by the lack of safety tolerance and the additional stress.